Ação coletiva e luta pela terra no assentamento Palmares II, Pará - MORENO, Glaucia de Sousa (Universidade Federal do Pará, 2021)
This dissertation examines how the actions taken by militants and participants of Palmares II Project Settlement, in Parauapebas-PA, contribute or not to consolidate a solidarity political practice in tune with MST ideals, since the camp through settlement phases. Data were collected between January and August 2010 through structured questionnaire used to interview leaders and settlers from the settlement into focus. The main work category is the collective action. It presents evidence that favored the formation and consolidation of the MST in Brazil, and later in Pará. Discusses the theoretical and empirical aspects of collective action in the movement, followed by a brief history of the development of the settlement, demonstrates and describes the collective actions that occurred during this period, brings into discussion contributions of America in Chicago school and from the Italian philosopher Antonio Gramsci. Describes collective efforts in the settlement occurred between 1996 and 2010, demonstrates how they developed, what goals and failures that marked this period, using the Olson, Mckean and Ostrom contributions to substantiate the discussion. Notes similarities and differences between the settlers projects and leaders of the movement, showing that some settlers had their projects "failed" due to the impositions of power play settlers / leadership. Points, in the research year, the collective initiatives that occurred in the settlement, which are assemblies and occupations, in order to resolve issues demanded by the necessity of settlement infrastructure and water supply improvement. Finally it states that it must think about the collective actions inside a project that aims farmers emancipation from a logic that works rooted in respect, first of all centered in settlers goals and needs, ie confined not in ideal models (averse to reality), but substantiated in the democratic conduct that strengthens the priorities settlers choice possibility. So first of all it should hear the agrarian reform actors, the landless or settlers, and not only allow the supposed leadership’s interests be taken into consider.